De la métaphore dans la langue informatique - Pirogowska, Ewa (Wydawnictwo Naukowe UAM, 2003)
The French of information science is a variant of a lively general language submitted to constant changes. In order to bring closer, better understand and get acqainted with the technical terms either names of equipment, programmes, or situations peculiar to computer reality, the user refers to everyday life (e.g. passerelle, English gateway; souris, English mouse) or to universal or mythological concepts (e.g. argonautes - internautes) thanks to the phenomenon of metaphor. It sometimes happens that the original concept, which served as a basis for the creation of a metaphor, is obliterated memory and computer users apply a new term being unaware of its origin. Just in this way during metaphoric operations totally new words are formed and they influence the specific character of the language of information science.
On metaphor in the language of information science
Keywords: Language of information science; Metaphor